Spatial Planning for Health Tourism Development in Belokurikha Resort - DUNETS, Aleksandr N.; ZHOGOVA, Inna G.; AKIMOV, Oleg S. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2019)
The health tourism development is of the greatest interest for the business sector and regional authorities in Altai Krai. To a great extent, tourist attractions are maintained and operate year-round. It should be noted that it is essential for the region, located in Siberia. In fact, Belokurikha Resort is the largest recreational area in the Asian part of the Russian Federation. Development of the resort has been subjected to the limits imposed by its location in a small valley of a mountainous river. Therefore, the commercial enterprises, local government and scholars are working on projects for the development of medical tourism within neighbouring territories of the resort. The authors of this paper suggest applying the frame approach in spatial planning for the territorial tourist complex “Bolshaya Belokurikha” (“Big Belokurikha”), and the main elements that are significant for the successful implementation of tourist projects are identified within. The use of the integrated approach allows for the consideration of stakeholders’ interests. To preserve the natural environment and further development of tourism, the natural park "Foothills of Altai" was established. This park is considered as a base of touristic operations. The concept and purpose of spatial development is to combine the development of medical tourism and rehabilitation into the natural environment. Currently, project proposals are being discussed by the working group of Altai Krai, and then they will be sent to the Ministry of Economic Development of the Government of the Russian Federation.